Green Treatment Strategies for Tannery Wastewater Employing Natural Polymers (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The leather tanning industry is one of the most water-intensive industrial sectors and generates highly polluted wastewater containing organic matter, inorganic salts, sulfides, chromium, and recalcitrant compounds. Conventional treatment methods rely heavily on chemical coagulants, which often produce non-biodegradable sludge and pose potential environmental and health risks. The present study investigates an eco-friendly and sustainable approach for tannery effluent treatment using a natural polysaccharide extracted from Strychnos potatorum L. seeds. The extracted polysaccharide was instrumentally confirmed using Fourier Transform Infrared (FTIR) spectroscopy, which revealed the presence of hydroxyl, carboxyl, and amine functional groups responsible for coagulation activity and SEM analysis of raw polysaccharide and treated sludge for the confirmation of coagulation process..Physicochemical characteristics of untreated tannery wastewater were analyzed and compared with treated samples following coagulation–flocculation using varying doses of the extracted polysaccharide. Process optimization studies identified an optimum coagulant dosage of 30 mg/L, rapid mixing at 120 rpm for 2 min, slow mixing at 40 rpm for 20 min, and a settling time of 30 min for maximum treatment efficiency. Significant reductions in turbidity, total suspended solids, chemical oxygen demand, and biological oxygen demand were observed, with maximum removals of 78% color, 62.5% total dissolved solids, 70% COD, and substantial reduction in suspended solids and BOD at the optimized dosage, demonstrating effective pollutant removal. The results highlight the potential of Strychnos potatorum seed polysaccharide as a biodegradable, low-cost alternative to conventional chemical coagulants. This green treatment strategy offers a promising pathway for sustainable tannery wastewater management and supports the transition toward environmentally responsible industrial practices.